Hetmańska Putzlaga - Mackiewicz, Paweł (1980- ).; Hetman, Grzegorz (1978- ). (2017)
Recenzja książki: Putzlaga i inne wiersze / Grzegorz Hetman. Wrocław, 2016.
Tytuł nagłówkowy.
Keywords: Książki -- recenzje -- 1990-.